Recognition of GT mismatches by Vsr mismatch endonuclease. - Fox, K; Allinson, S; Sahagun-Krause, H; Brown, T (2000)
The Vsr mismatch endonuclease recognises the sequence CTWGG (W = A or T) in which the underlined thymine is paired with guanine and nicks the DNA backbone on the 5'-side of the mispaired thymine. By using base analogues of G and T we have explored the functional groups on the mismatch pair which are recognised by the enzyme. Removal of the thymine 5-methyl group causes a 60% reduction in activity, while removing the 2-amino group of guanine reduces cleavage by 90%. Placing 2-amino-purine or nebularine opposite T generates mis-matches which are cut at a much lower rate (0.1%). When either base is removed, generating a pseudoabasic site (1', 2'-dideoxyribose), the enzyme still produces site-specific cleavage, but at only 1% of the original rate. Although TT and CT mismatches at this position are cleaved at a low rate (approximately 1%), mismatches with other bases (such as GA and AC) and Watson-Crick base pairs are not cleaved by the enzyme. There is also no cleavage when the mismatched T is replaced with difluorotoluene.